Whitman and the Irish - Krieg, Joann P. (Iowa Whitman series., 2000)
Though Walt Whitman created no Irish characters in his early works of fiction, he did include the Irish as part of the democratic portrait of America that he drew in Leaves of Grass. He could hardly have done otherwise. In 1855, when the first edition of Leaves of Grass was published, the Irish made up one of the largest immigrant populations in New York City and, as such, maintained a cultural identity of their own. All of this "Irishnesso swirled about Whitman as he trod the streets of his Mannahatta, ultimately becoming part of him and his poetry.